2016
DOI: 10.1093/nar/gkw748
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 is targeted for proteasomal degradation by the E3 ligase FBW7 in response to DNA damage

Abstract: SOX9 encodes a transcription factor that governs cell fate specification throughout development and tissue homeostasis. Elevated SOX9 is implicated in the genesis and progression of human tumors by increasing cell proliferation and epithelial-mesenchymal transition. We found that in response to UV irradiation or genotoxic chemotherapeutics, SOX9 is actively degraded in various cancer types and in normal epithelial cells, through a pathway independent of p53, ATM, ATR and DNA-PK. SOX9 is phosphorylated by GSK3β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 83 publications
2
44
0
Order By: Relevance
“…However, whether other members of the Sox family are involved in maintaining hepatic lipid homeostasis is worth studying. Especially, recent studies demonstrated that ubiquitination-mediated protein stability and degradation have an important role for the aberrant expression of SOX9 in human malignancy (40,41). Besides, a methylation-phosphorylation switch controls SOX2 protein stability in embryonic stem cell differentiation (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether other members of the Sox family are involved in maintaining hepatic lipid homeostasis is worth studying. Especially, recent studies demonstrated that ubiquitination-mediated protein stability and degradation have an important role for the aberrant expression of SOX9 in human malignancy (40,41). Besides, a methylation-phosphorylation switch controls SOX2 protein stability in embryonic stem cell differentiation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Small-molecule inhibitors of the PI3K/mTOR pathway can be used to stimulate GSK3/FBW7a-mediated SOX9 turnover and may provide a novel strategy to target SOX9-driven medulloblastoma. (Hong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described (28). Xenograft tumor samples were snap-frozen in liquid nitrogen and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%